Lactate-Protected Hypoglycemia (LPH) - Goodwin, Matthew L.; Gladden, L. Bruce; Nijsten, Maarten W. N. (Frontiers in Neuroscience, 2020)
Here, we provide an overview of the concept of a lactate-protected hypoglycemia (“LPH”), originally proposed as lowering glucose while simultaneously increasing lactate concentration as a method by which tumors might be targeted. Central to this hypothesis is that lactate can act as a critical salvage fuel for the central nervous system, allowing for wide perturbations in whole body and central nervous system glucose concentrations. Further, many tumors exhibit “the Warburg” effect, consuming glucose and producing and exporting lactate despite adequate oxygenation. While some recent data have provided evidence for a “reverse-Warburg,” where some tumors may preferentially consume lactate, many of these experimental methods rely on a significant elevation in lactate in the tumor microenvironment. To date it remains unclear how various tumors behave in vivo, and how they might respond to perturbations in lactate and glucose concentrations or transport inhibition. By exploiting and targeting lactate transport and metabolism in tumors (with a combination of changes in lactate and glucose concentrations, transport inhibitors, etc.), we can begin developing novel methods for targeting otherwise difficult to treat pathologies in the brain and spinal cord. Here we discuss evidence both experimental and observational, and provide direction for next steps in developing therapies based on these concepts.